Controlled pore growth for enhanced photoluminescence of ceramic phosphors. (September 2021) - Ratzker, Barak; Wagner, Avital; Kalabukhov, Sergey; Frage, Nachum
Abstract: Ceramic phosphors have great potential as high-power color converters for solid-state lighting. The strive for developing increasingly bright and efficient phosphors stimulates research on scattering effects within phosphor media to enhance photoluminescence (PL). In the present study, we demonstrated a simple manner to improve PL properties of Ce:YAG transparent ceramic phosphors fabricated by spark plasma sintering. Controlled pore growth was achieved by post-sintering heat treatments, utilizing high-pressured gas trapped within residual pores to induce swelling. After heat treatment, the emission intensity and efficiency increased substantially. This is a promising method for microstructure tailoring to enhance PL and realize more effective ceramic phosphors. Graphical abstract: Image, graphical abstract